(untitled) (REVISTA NODO, 2017)
the relationship between women and public space refers, on the one hand, to the paradigmatic public / private dichotomy in which the fundamental roles of men and women are outlined, with all their implications for the use and city enjoyment; and on the other hand, it is crossed by the multiple structural inequalities suffered by females in the bosom of society, which are also configured and visible in urban public districts. It is from this perspective that this article is framed, whose fundamental purpose is to ponder over the places that women occupy in city life, starting from the fact that they have been historically erased from the public sphere, and confined in the realm of the occult, the invisible, the unnamable. It is in this sense, that the notion of a public space, so desired by some city planners and developers, is associate with democracy, accessibility and asepsis; qualities that only seem to be present in their unifying gazes with a clear patriarchal tinge. thus, is not possible to ignore the unequal and discriminatory social structures –based on age, ideology, class, ethnic identification, gender– that make up the urban public districts and dispel the idea that in these, all human beings can enjoy the fundamental rights and approach effectively to those notions of democracy and freedom, so exalted in present cities.